Turning Hard Problems into Post-quantum Solutions - Matthews, Gretchen (American scientist, 2024)
Today, mathematicians, computer scientists, engineers, and others are rushing to find what my dad luckily did not have to: problems that are hard for both classical and quantum computers to soke. Present-day cryptography is based on mathematical problems that are time-consuming for classical machines. Hackers try to solve these problems to extract raw data from its encrypted form. As computational speed increases, we make the problems longer, just like my dad did. Up to this point, making small adjustments and cleverly expounding upon previous ideas has been sufficient. Cryptography is an ancient secret-keeping practice. The word is derived from the Greek krypk, which means to keep hidden, and graphia, which means writing. It is the art and science of obscuring information (text or numerical data) in such a way that it becomes unreadable. It is used in powerful ways behind the scenes to allow secure communications, financial transactions, and blockchain ledgers used to validate bitcoin transactions.